Weekend versus weekday admission and short-term mortality: A meta-analysis of 88 cohort studies including 56, 934, 649 participants. Issue 17 (April 2017) - Hoshijima, Hiroshi; Takeuchi, Risa; Mihara, Takahiro; Kuratani, Norifumi; Mizuta, Kentaro; Wajima, Zen'ichiro; Masaki, Eiji; Shiga, Toshiya
Abstract : Abstract: It is widely accepted that higher mortality related to weekend admissions basically exists; however, there has been no systematic exploration of whether weekend admissions are associated with higher risk of death in patients on the basis of certain diagnoses, geographic regions, and study subtypes. A meta-analysis was performed according to the reporting guidelines of the Meta-analysis of Observational Studies in Epidemiology (MOOSE Compliant). Literature search was conducted using electronic databases. Primary outcome was short-term (⩽30-day) mortality. Patients were divided into 7 regions (North America, South America, Europe, Asia, Oceania, Africa, and Antarctica) for subgroup analyses and into 7 categories evaluating 24 major diagnoses. Pooled odds ratio (OR) with 95% confidence interval (CI) was calculated with DerSimonian and Laird random-effects models. Eighty-eight studies including 56, 934, 649 participants met our inclusion criteria. Overall pooled adjusted and crude OR of weekend to weekday admission for short-term mortality was 1.12 (95% CI, 1.07–1.18; I 2  = 97%) and 1.16 (95% CI, 1.14–1.19; I 2  = 97%), respectively. In subgroup analyses, higher risk of death on the weekend was significantly identified in patients living in all five continents (North America, South America, Europe, Asia, and Oceania). However, significant weekend effect was identified only in 15 of 24 diagnostic groups. Patients admitted on the weekend were more likely to die in an emergency situation (crude OR = 1.17, 95% CI, 1.12–1.22). Although weekend admissions were associated with higher risk of death compared with weekday admissions on all five continents, the effect was limited to certain diagnostic groups and admission subtypes. Weekend effect remains highly heterogeneous and limited, suggesting that further well-conducted cohort studies might be informative. Abstract : Supplemental Digital Content is available in the text